Identificação organizacional como principal estratégia de retenção de jovens numa empresa de consultoria de IT: construção de um plano de retenção para a empresa - Machado, Carolina Dias (2019)
The purpose of this project is to show that Organisational Identification can be used as a main strategy to retain young professionals in the IT Consulting business. At the end of the project, a Retention Plan is expected to be constructed for Company A. For data collection, 10 semi-structured individual interviews and 1 focus group of 5 people were conducted. The participants consisted of young people, who already are a part of the Academy Project at the company where the plan is to be implemented and who already are inserted in the job market. The empirical research methods used were qualitative, and two separate content analysis were conducted – one of them to evaluate the information obtained in the interviews and the other for the focus group. Based on the result analysis, we were able to understand that the young people involved value four dimensions: organisational identification with company A, their relationship with company B, salary and benefits and the balance between professional and social life. The conclusions drawn were fundamental to reach the main purpose of the project: the construction of a retention plan for young workers at company A.